Conceptualizations of Africa
X, 421 p. 2 illus., 1 illus. in color.
Keywords: This book discusses how Africa has been understood and defined across various academic fields. Building on the influential works of Valentin-Yves Mudimbe and more recent studies by Axel Fleisch and Rhiannon Stephens, this book bridges previous limitations by offering a comprehensive, interdisciplinary analysis. Each chapter examines the conceptualization of Africa within a specific discipline, balancing local and global perspectives, blending competing viewpoints, and providing suggestions for future research. The book will be essential for students, scholars, and researchers interested in a better understanding of the diverse and complex narratives that shape our knowledge of Africa and its intellectual heritage.